CONSTRUCTING RELIGIOUS DISCOURSE IN THE DIGITAL ERA: A CRITICAL DISCOURSE ANALYSIS OF PUBLIC RELATIONS STRATEGIES AT IAIN PAREPARE - Suherman, Suherman; Mujahidah, Mujahidah (IAIN Manado, 2025)
In the era of information disruption, State Islamic Higher Education Institutions (PTKIN) face challenges in maintaining religious authority in the virtual public sphere. This study aims to analyze the strategy of IAIN Parepare’s Public Relations in constructing the discourse of religious moderation through digital media. Using a qualitative method with a Critical Discourse Analysis approach, this study dissects the text dimensions, discourse practice, and social practice of the campus’s digital activities. The results show that IAIN Parepare’s Public Relations acts not only as an administrative information manager but also as a strategic knowledge producer. The findings reveal: 1) Digital infrastructure (website, Facebook, Instagram, YouTube) serves as a power tool to produce authoritative religious narratives; 2) At the textual level, Public Relations applies a strategy of vernacularization of moderation values by integrating Bugis local wisdom terms, such as “Panrita” and “Malebbi,” in its digital da’wah programs; 3) At the social practice level, there is a transformation of communication from a one-way corporate pattern to a dialogic-participatory one, implying the strengthening of social legitimacy and the institution’s positive image as a center of religious moderation.Keywords: Digital Public Relations; Religious Moderation; Critical Discourse Analysis; Social Media; Local WisdomAbstrak: Di tengah era disrupsi informasi, Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) menghadapi tantangan dalam mempertahankan otoritas keagamaan di ruang publik virtual. Penelitian ini bertujuan untuk menganalisis strategi Humas IAIN Parepare dalam mengonstruksi wacana moderasi beragama melalui media digital. Menggunakan metode kualitatif dengan pendekatan Analisis Wacana Kritis (Critical Discourse Analysis), penelitian ini membedah dimensi teks, praktik produksi wacana, dan praktik sosial dari aktivitas digital kampus. Hasil penelitian menunjukkan bahwa Humas IAIN Parepare tidak hanya berperan sebagai manajer informasi administratif, melainkan sebagai produsen pengetahuan yang strategis. Temuan mengungkapkan: 1) Infrastruktur digital (website, Facebook, Instagram, YouTube) difungsikan sebagai alat kekuasaan untuk memproduksi narasi keagamaan yang otoritatif; 2) Pada level teks, Humas menerapkan strategi vernakularisasi nilai moderasi beragama dengan memadukan istilah kearifan lokal Bugis, seperti “Panrita” dan “Malebbi”, dalam penamaan program dakwah digitalnya; 3) Pada level praktik sosial, terjadi transformasi komunikasi dari pola korporat satu arah menjadi dialogis-partisipatif, yang berimplikasi pada penguatan legitimasi sosial dan citra positif institusi sebagai pusat moderasi beragama. Kata Kunci: Humas Digital; Moderasi Beragama; Analisis Wacana Kritis; Media Sosial; Kearifan Lokal